Analisis Dan Perancangan Sistem Informasi Inventaris Barang Pada SMP Negeri 2 Kota Jambi - Muhidin, Muhidin; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2020)
In a government agency, can not be separated from an inventory process. This inventory process with the purpose of asset data items that exist in the institution. The need for a system of mutual information integrity in process inventory that existed at the SMPN 2 of Jambi City. Because at this time the inventory process is still using a manual system, thus causing errors in inputting and reporting inventory. This item inventory system by using modeling UML (Unified Modeling Language) using this model is able to explain the needs of the system and the flow of the system to be analyzed for the inventory system of goods in this instance.